Distribution of useful species of family Rosaceae Juss in the flora of Zhetysu Alatau - Aidarbayeva, D.K.; Taldybay, A.A.; Kaly, A; Uvaliyev, T.O.; Demeuova, L.N. (Fundamental and Experimental Biology, 2024)
In the article the results of an analysis of the species composition of wild plants of the Rosaceae Juss family were presented. As a result of floristic analysis, it was established that in the northwestern part of the Zhetysu Alatau there are 91 species belonging to the Rosaceae family, belonging to 24 genera. The leading genera in this area are: Potentilla — 24, Cotoneaster — 9, Rosa -9, Alchimilla -7, Crataegus — 5, etc. According to ecological and morphological classifications, all useful species were ranked into 4 groups (trees, shrubs, subshrubs, herbaceous perennials). Spectra of useful properties were shown (use in scientific medicine and in folk medicine, such as vitamins, decorative, food, etc.). 12 groups of medicinal types were ranked according to pharmacotherapeutic activity.